2017
DOI: 10.1002/ejhf.789
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic importance of left ventricular mechanical dyssynchrony in heart failure with preserved ejection fraction

Abstract: Aims Left ventricular (LV) mechanical dyssynchrony has been described in heart failure with preserved ejection fraction (HFpEF), but its prognostic significance is not known. Method and Results Of 3445 patients with HFpEF enrolled in the Treatment of Preserved Cardiac Function Heart Failure With an Aldosterone Antagonist TOPCAT trial, dyssynchrony analysis was performed on 424 patients (12%) by multiple speckle-tracking echocardiography strain-based criteria. The primary dyssynchrony analysis was the standar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(11 citation statements)
references
References 42 publications
0
11
0
Order By: Relevance
“…In HFpEF patients, LV mechanical dyssynchrony has been suggested to contribute to an impairment of longitudinal systolic and diastolic LV function and to be associated with higher LV-filling pressures and worse clinical status in terms of NYHA functional class [ 145 ]. On the other hand, a post hoc analysis of the TOPCAT trial has shown that LV mechanical dyssynchrony is not associated with outcomes of HFpEF patients [ 146 ]. Targeting LV dyssynchrony by implantation of a CRT device is currently subject of ongoing studies, which will help to better understand its relevance for the therapy of HFpEF patients (NCT03338374, NCT02145351).…”
Section: Treatment Of Hfpefmentioning
confidence: 99%
“…In HFpEF patients, LV mechanical dyssynchrony has been suggested to contribute to an impairment of longitudinal systolic and diastolic LV function and to be associated with higher LV-filling pressures and worse clinical status in terms of NYHA functional class [ 145 ]. On the other hand, a post hoc analysis of the TOPCAT trial has shown that LV mechanical dyssynchrony is not associated with outcomes of HFpEF patients [ 146 ]. Targeting LV dyssynchrony by implantation of a CRT device is currently subject of ongoing studies, which will help to better understand its relevance for the therapy of HFpEF patients (NCT03338374, NCT02145351).…”
Section: Treatment Of Hfpefmentioning
confidence: 99%
“…Left ventricular electrical dys‐synchrony is a strong prognostic marker of adverse outcomes in heart failure with reduced EF . With STE, LV mechanical dys‐synchrony can be detected as peak systolic dispersion (PSD), calculated as the standard deviation of the time to peak strain of the 18 segments, divided by the RR interval . Studies have shown that strain‐derived mechanical dys‐synchrony abnormalities are independently associated with LVEF changes over time in regard to idiopathic dilated cardiomyopathy, as well as the occurrence of ventricular tachycardia after myocardial infarction (MI) …”
Section: Introductionmentioning
confidence: 99%
“…Biering‐Sørensen et al conducted a study on 3445 patients with HF and preserved EF, and they reported MD in 12% of the patients. However, MD did not predict poor outcomes.…”
Section: Discussionmentioning
confidence: 99%